Sustained Harvest of Bobwhite Populations - John L. Roseberry (National Quail Symposium Proceedings, 2017)
(Invited Paper) Sport hunting is an important aspect of wildlife management, yet the principles of game harvesting seem not to be particularly well understood or accepted by many in the wildlife profession. This paper examines the two major harvest theories as they apply to the bobwhite. The sustained yield approach is considered conceptually superior to the popular annual surplus theory. Wildlife management admittedly involves practical as well as theoretical considerations; nevertheless, it is important that harvest policy be based on sound scientific principles and guided by clear objectives. To do otherwise puts both the resource and our own professional credibility at risk.